Interdependence of the Interests of the United States, China and Russia in Central Asia - A. V. Toropygin; A. E. Mendagaziev (Евразийская интеграция: экономика, право, политика, 2020)
Central Asia is the union republics of former Central Asia and Kazakhstan, which became independent countries after the USSR collapse. The formation of new states and regions is associated with both internal challenges and the influence of external extra-regional forces. The purpose of the article is analyzing the interests and influence of the United States, China, and Russia on the Central Asia development, as well as the perception of these forces in the region. Various stages of this influence from the moment of its appearance to the present time are analyzed. The authors concluded that the countries of Central Asia during its independent existence perceived powers in the triangle USA — Russia — China differently, which was a prerequisite for the formation of their multi-vector foreign policy. The balance of interests of Russia’s, the United States’ and China’s presence in the region is vital for the Central Asian countries, it provides an independent foreign policy course and development of Kazakhstan, Uzbekistan, Kyrgyzstan, Turkmenistan and Tajikistan, contributing to a stable situation in the region.